Punching shear tests of post‐tensioned flat slabs supported on edge columns. (6th December 2019) - Barbán, Vladimir V.; Melo, Guilherme S.; Carvalho, Alessandra L.
Abstract: This paper describes an experimental study of the punching resistance of unbonded post tensioned flat slabs supported on edge columns. Fifteen slabs rectangular in plain, with sides of 2 m by 1.2 m and 120 mm thick were tested, supported on square columns with sides of 200 mm and with length of 600 mm at the top and at the bottom. The main variables are the eccentricity ( M u / V u ) of the shear force, which is obtained varying the relation between loads parallel and perpendicular to the free edge; the amount of unbonded tendons (4 or 6 tendons perpendicular to the free edge and 3 or 2 tendons parallel to the free edge with the column); and the non‐prestressed flexural reinforcement detailing. The behavior of slabs is discussed in terms of vertical displacements, strains on concrete and on non‐prestressed rebars, forces on the unbonded tendons, cracking pattern and ultimate shear forces. The increase of the eccentricity ( M u / V u ) changes the failure mode from punching to flexure and torsion associated to punching.